Constitutionality Of The Existence Of Land Banks In The Management And Control Of Land By The State - Putri, Mega Mutiara (LEGAL BRIEF, 2025)
This paper looks at the legal concerns surrounding the effects of land bank rules on governmental control and management of land. Using normative legal research techniques, it was discovered that Government Regulation Number 64 of 2021 concerning the Land Bank Agency regulates the establishment of a land bank, which is governed by Article 125-135 of Law Number 6 of 2023 concerning the Stipulation of the Job Creation Regulation. The regulation relating to the Land Bank in PP Number 64 of 2021 concerning the Land Bank Agency has legal ramifications because it conflicts with the 1945 Indonesian Constitution, specifically Article 6 letter a and Article 7 of PP Number 64 of 2021 concerning the Land Bank Agency regarding land. This is because the government determined that land control by the state is covered by Article 33 paragraph (3) of the 1945 Constitution. Because they went against the Constitution's guarantee of the State's authority, the two Articles are incompatible